A Simple Mathematical Model for Covid-19: Case Study of Goa - Mazumdar, Neeta; D’Costa, Rachel Sarah; Kauthankar, Sanjala Sanjay; Rebello, Shielda Vanisha (Communications in Mathematics and Applications, 2023)
This paper analyses a simple SEIR model (Susceptible-Exposed-Infected-Removed) to study the impact of the Covid-19 pandemic on Goa. A system of non-linear ODE has been used. The system is analysed using stability analysis. Novel Corona Virus (Covid-19) was declared a pandemic on 11th March 2020. Thereon India has witnessed three Covid-19 waves from March 2020 to March 2022. To control the subsequent impact on our livelihoods, it is of utmost need to study the spread of the virus. The findings of the model will then be compared to the recorded data of the 1st and 2nd waves of the neighbouring states of Maharashtra and Karnataka. Further, it will be shown how the probability of effective exposure and the per-capita contact rate influences the healthy and infected population. The proposed model can be used to make predictions for subsequent waves if any, in Goa.